**Решение:**
1. Поскольку \(\angle MSB\) и \(\angle MSA\) - смежные, их сумма равна \(180^\circ\). Следовательно, \(\angle MSA = 180^\circ - 108^\circ = 72^\circ\).
2. Так как SM - биссектриса угла ASN, то \(\angle ASN = 2 \cdot \angle MSN\). Также \(\angle ASN\) и \(\angle MSA\) - смежные углы. Значит, \(\angle ASN + \angle MSA = 180^\circ\).
3. Тогда \(\angle ASN = 180^\circ - \angle MSA = 180^\circ - 72^\circ = 108^\circ\).
4. Так как SM - биссектриса угла ASN, то \(\angle NSM = \frac{1}{2} \cdot \angle ASN = \frac{1}{2} \cdot 108^\circ = 54^\circ\).
**Ответ:** \(\angle NSB = 54^\circ\)
Убрать каракули